Which Flexible Ureteroscopes (Digital vs. Fiber-Optic) Can Easily Reach the Difficult Lower Pole Calices and Have Better End-Tip Deflection: In Vitro Study on K-Box. A PETRA Evaluation - ŞENER, TARIK EMRE (MARY ANN LIEBERT, INC, 2017)
Background and Purpose: Modern flexible ureteroscopes (fURSs) have good deflection, but despite this, approaching an acute angled calix can still be difficult. The goals of our in vitro study were to assess the ability of the available modern fURSs to effectively access the sharp angled calices and to compare the end-tip deflection of the various fiber-optic and digital fURSs. Materials and Methods: Using a bench-training model for FURS (K-Box, Porge's-Coloplast), we tried to access an acute angled calix with nine different fURSs (BOA vision, COBRA vision, R. Wolf; FLEX X-2, FLEX Xc, K. Storz; LithoVue, Boston Scientific; URF-P5, URF-P6, URF-V, URF-V2, Olympus). Passing the fURSs through a ureteral access sheath (ReTrace, Porge's-Coloplast), the maximum end-tip deflection for every fURS was measured with the tip extended out from the sheath at 1, 2, 3, and 4 cm. Two ranking methods were designed for scoring the fURSs, one based on total ranking points and the other on total degrees of deflection. Results: While all fiber-optic fURSs (except URF-P6) were able to access the sharp angled calix, none of the digital fURSs (except FLEX Xc) reached the difficult angled calix. Similarly, all fiber-optic fURSs had better end-tip deflection compared with the digital fURSs, except FLEX Xc, which was as deflectable as the fiberoptic fURSs. The fURSs showed an end-tip deflection (median difference of almost 21 degrees) in favor of fiber-optic fURSs. Based on the scoring, the highest ranked fURS (best deflection) was FLEX X2 and the lowest ranked fURS (worst deflection) was URF-V2. Conclusions: Digital fURSs were less effective in accessing the sharp angled calix and they had lesser end-tip deflection compared with the fiber-optic counterparts. When approaching a difficult lower pole calix, it might be better to use a fiber-optic fURS.
Keywords: flexible ureteroscopes; end-tip deflection; acute angled calices; IRRIGATION FLOW; URETERORENOSCOPE